AB1080 Comparison of Physical Function in SLE and RA Using Mdhaq. (10th June 2014) - Annapureddy, N.; Giangreco, D.; Shetty, N.; Pincus, T.; Block, J.A.; Jolly, M.
Abstract : Background: The rheumatic diseases have significant impact on patients' physical function. Patient reported outcome (PRO) tools provide insight into physical function, and are the most significant clinical predictor of work disability and premature mortality in rheumatoid arthritis (RA). (1) The multi-dimensional health assessment questionnaire (MDHAQ) provides valid, quick and comprehensive assessment of functional status. Objectives: We compared the performance of the physical function (FN) component of MDHAQ in Systemic Lupus erythematosus (SLE) vs. RA. Methods: 70 female patients meeting ACR criteria for SLE and 70 female patients meeting criteria for RA completed MDHAQ during a routine clinic visit. We had all female patients for consistency between the two groups. We performed exploratory factor analysis (Principal Component analysis with varimax rotation) on the 13 items in the FN items, along with determination of floor and ceiling effects for SLE and RA. We compared the results for SLE and RA. We then excluded items with significant cross- loadings on factor analysis, and/or showed floor or ceiling effect of greater than 65%. Traditional FN (8 items from the original HAQ (a-h), 2 complex activities (I, j), and 3 psychological items (k-m), added in 1999) (2) and composite brief FN (bFN) from the remaining items excluding the psychological items (k-m) and then normalized to a scale of 0-10 using the remaining FN items. Performance of the bFN against the FN score was determined using linear regression in SLE and RA, with FN as the dependent and bFN as the independent variable. Variability in FN (R 2 ) explained by bFN in this regression model was assessed separately for SLE and RA. A p value of ≤0.05 was considered statistically significant on two tailed tests. Results: Mean (SD) ages of the SLE and RA patients were 45.1 (14.0) and 41.1 (9.0) yrs., respectively. The mean (SD) FN were 1.7 (1.9) and 2.5 (2.0) respectively in SLE and RA patients. Most items loaded into 3 factors [Table 1, reflecting the original design (2)]: factor 1- activities of simple living (a-h in SLE and items a-c, e-g in RA), factor 2-activities of complex living (i and j) and factor 3 - psychological (k-m). In RA, items 1d loaded onto factor 2 and item 1h cross-loaded onto both factors 1 and 2. After removing cross-loading items (h) and items with >65% (b, c, d, e, g), four items of the original FN remained (a, f, i, j); these items significantly and clearly loaded into one of the two factor components in SLE, and identical findings were noted for RA. bFN from these 4 items explained 87.9% (P<0.001) and 88.2% of variance (p<0.001) in SLE and RA respectively. Conclusions: Most of the items in the FN of MDHAQ loaded onto similar factors in SLE and RA and the performance was comparable. bFN captured close to 90% of the information derived from the 10 items of traditional FN in both SLE and RA. This information may help shorten the current questionnaire or allow inclusion of newer items with better measurement properties in the future. References: Sokka T, Abelson B, Pincus T. Mortality in rheumatoid arthritis: 2008 update. Clin Exp Rheumatol 26 (Supplement 51):S35-S61, 2008. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4825